2022
DOI: 10.2340/17453674.2022.2583
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic surgical procedures in 3,305 children and young adults with cerebral palsy: a register-based cohort study

Abstract: Background and purpose: Few reports have described the panorama of orthopedic surgeries that children with cerebral palsy (CP) undergo. We analyzed the risk of a first surgery, and describe the frequency of orthopedic surgeries in terms of age, sex, anatomical location, and Gross Motor Function Classification System (GMFCS) level in children and young adults with CP.Patients and methods: This was a register-based cohort study of 3,305 individuals followed until 2–25 years of age. We used data from 2 national S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
1
9
1
Order By: Relevance
“…While this is congruent with our study, it is important to note that the European study had a much smaller population size of patients that underwent surgical intervention compared to our study, and the mean age of operation in the Swedish group was 5.7 years old, while our youngest age group only went to age four. A larger study also conducted in Sweden including 3,305 children and adolescents similarly demonstrated that those less than 15 years of age more frequently underwent surgical procedures and had lower gross motor function scores, corroborating the early intervention seen in our study [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…While this is congruent with our study, it is important to note that the European study had a much smaller population size of patients that underwent surgical intervention compared to our study, and the mean age of operation in the Swedish group was 5.7 years old, while our youngest age group only went to age four. A larger study also conducted in Sweden including 3,305 children and adolescents similarly demonstrated that those less than 15 years of age more frequently underwent surgical procedures and had lower gross motor function scores, corroborating the early intervention seen in our study [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…The optimal timing of surgical intervention in children with CP is difficult to determine. [16][17][18][19] With a lack of knowledge on the evolution of foot posture during childhood, it is a challenge to predict improvement or progression of deformity. Poorly timed surgery poses a threat of deformity recurrence or overcorrection with the potential need for revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention can have a dramatic impact on foot deformities in children with CP. 15 , 32 Telléus et al 18 describe foot and ankle surgeries as the most common procedures in people with CP between the ages of 2 and 25 years, accounting for 49% of procedures in those classified as GMFCS level I, 54% of people classified as level II, and 40% in those classified as level III. Our study shows comparable results where 35% of surgeries in children classified as level I, 29% classified as level II, and 40% as level III included foot correction procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankle and foot surgery was predominant as the first surgery in GMFCS I-II patients, hip and femur surgery in GMFCS IV-V patients, while spine surgery was mainly performed in GMFCS IV-V patients. Overall, it was found that the risk of undergoing first orthopaedic surgical treatment increased with increasing GMFCS level, and it was performed at a younger age in children with a higher GMFCS level [ 52 ].…”
Section: Introductionmentioning
confidence: 99%